2011
DOI: 10.1002/adma.201102124
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Albumen Dielectrics in Organic Field‐Effect Transistors

Abstract: The application of the biomaterial dielectrics made of thermally crosslinking natural proteins without any additives in fabricating organic electronics is highlighted. The gate dielectrics of organic field‐effect transistors (OFETs) are prepared by the thermal treatment of the chicken albumen film taken directly from a fresh egg. Flexible OFETs and the complementary inverters fabricated with albumen dielectrics are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(136 citation statements)
references
References 19 publications
(21 reference statements)
3
129
0
Order By: Relevance
“…357 The dielectric layer is produced by the thermal cross-linking. 358 Flexible pentacene and C 60 -based OFETs fabricated with albumen dielectrics demonstrated output currents significantly higher compared to the equivalent devices with poly(methyl methacrylate) (PMMA) dielectric.…”
Section: Chemical Reviewsmentioning
confidence: 97%
“…357 The dielectric layer is produced by the thermal cross-linking. 358 Flexible pentacene and C 60 -based OFETs fabricated with albumen dielectrics demonstrated output currents significantly higher compared to the equivalent devices with poly(methyl methacrylate) (PMMA) dielectric.…”
Section: Chemical Reviewsmentioning
confidence: 97%
“…For instance, Uemura et al developed the synthetic polypeptide poly (γ-methyl-L-glutamate) (PMLG), as the gate dielectric to prepare the organic field effect transistor memory as early as 2001 [22]. Jer-Wei Chang et al [23] and So-Jung Kim et al [24] demonstrated OTFTs based on chicken albumen as the gate dielectric. Recently, base pairs of DNA have also been applied as gate insulators in OTFTs as presented below.…”
Section: Dna As Functional Layers For Otftsmentioning
confidence: 99%
“…Advanced n-type organic transistors and light emitting transistors have successfully been built up by using natural silk fibroin, whose degradation lifetime may range from weeks to years [36]. The easily obtainable and inexpensive natural compound chicken albumin is utilized as gate dielectric in OFETs, too [37]. The spin-coated and thermally treated, unmodified material generates high quality thin films for devices with excellent performance.…”
Section: Dielectric Materialsmentioning
confidence: 99%